The heroic childhood theme in Virgil’s ‘Aeneid’: the cases of Ascanius-Iulus and Camilla, the Queen of the Volci - Mota, Thiago Eustáquio Araujo (Romanitas - Revista de Estudos Grecolatinos, 2020)
This article aims to investigate the poetic appropriations of the theme of heroic childhood from the construction of the characters Ascanius-Iulus and the Volscian queen, Camila, in Aeneid Although projected in the heroic age, or in the pre-foundational past, the Virgilian epic reveals important aspects of the Roman perception about the formative phases known as infantia, pueritia and pubertas and about the respective gender roles. In this way, we seek to investigate in which terms the Virgilian heroes perform or transgress these stages, either by excellence or by deviation.